Optimum design for an incomplete second degree mixture model. (2019) - Mandal, Nripes K.; Pal, Manisha
Mixture experiments form an important part of research in areas like pharmaceutical, biometrics, agriculture, etc. Optimum mixture designs have been derived by many authors for mixture models due to Scheffé (1958) and others. In most of these models, there is no discrimination among the components. However, in practice, the situation may be quite different. In this paper, we have considered a situation where some but not all of the interaction terms are present. Optimum designs have been determined for the estimation of parameters of a second degree model. Finally, optimum designs for prediction have also been considered.